(untitled) (Journal of the College of Education for Women, 2019)
This research paper is about synoptic climate specifically with in the upper air layersusing upper air layers maps analysis which are maps of thickness for the level 1000 – 500MB, that their high average ranges between 100 – 5600 M above surface. This research paperfocuses on studying special and temporal variations of the atmosphere thickness above Iraqaccordingto this study, it is concluded that atmosphere thickness above Iraq increasestowards south with an average of 100 M as compared with north of Iraq. Regarding thetemporal variations, it is concluded that atmosphere thickness during hot months. In July, forexample, the atmosphere thickness becomes thicker than in January with an average of(250)M in Iraq. It is also found at atmosphere thickness above Iraq increases in recent years,especially in Baghdad.When the atmosphere thickness reaches (5400)M, It is an indication of air front formationon the surface. So, a follow up procedure of these locations above Iraq, which is representedby a line on the weather maps, was used. It appears that the line direction moves away fromIraq and goes toward Turkey in recent years, which means that air north, too.By analyzing the weather maps of pressure air systems (1000)MB accompanied with linethickness, it appears that air depressions mostly accompanies with line thickness (5400)M .Whereas, within the pressure level maps (500)MB, It appears the upper trough of the airdepression the most frequent pressure system with thickness line of (5400)M.